A study on the implementation of Occupational Safety And Health Acts (OSHA) towards employee's performance at Silverstone Berhad, Perak / Nurul Hanani Ishak - Ishak, Nurul Hanani (2014)
The purpose of this study is to identify the factors influencing the implementation of Occupational Safety and Health Acts (OSHA) towards employee's performance. The selected organization is at Silverstone Berhad , Kamunting, Perak, Malaysia. Pearson's correlation was used in the correlation coefficient method to find the result on relationship existence between the variables. The researcher has focused on the office staff for the sampling size at Silverstone Berhad with the population 300 employees and by using simple random sampling techniques, 120 respondents were decided by researcher to distribute questionnaire and I00 respondents has given feedback. Besides that, Cronbach's alpha is also used to measure the reliability for each variable in the questionnaire. Cronbach's alpha, which is based on the average correlation of items within a test if the items are standardise. The unit of analysis is individual with the instrument Likert Scale question. Therefore, the questionnaire is udes to collect the data and Statistical Package for Social Science (SPSS) version 20.0 is used to compute the findings and result of the variables. This research study will make an important issue and will contribute to government, private company, and employee itself. The result of the research shows that all independent variables are positive significant with the dependent variables thus, the hypothesis were accepted.